Professional Development in Technology Integration Among Teacher Educators in Ghana - Mudasiru Olalere Yusuf; Seth Dade Ansah; Talatu Fahdilat Ahmed; Hamdallat Taiwo Yusuf (Indonesian Journal Of Educational Research and Review, 2022)
In this digital era, education makes learners acquire the appropriate and relevant knowledge, attitude and skills that lead to understanding and functioning well in their digitally dominated environment. This research explored how exemplar lecturers developed competencies and skills in integrating technology for instruction. A qualitative hermeneutic phenomenology design was used for the study. In all, 20 lecturers (exemplars) out of 327 lecturers from a teacher education university in Ghana formed the sample and were interviewed by one of the researchers for ten weeks. Data were analysed using thematic coding, structural coding, pattern coding and focused coding in arriving at exemplars' experiences. The findings show that exemplars integrated ICTs such as Google Application for Educators (GAFE), Microsoft Office and Education tools, and other open-source software to make them stand out among their colleagues, as exemplars. Exemplars acquired their integration competencies through individual learning, colleagues, and online materials. The findings underscored the need for institutional facilities provision and support to deepen ICT integration in universities. Based on the results, recommendations, implications, and limitations are discussed.